Membrane independent activation of fibroblast proMMP-2 by snake venom: novel roles for venom proteinases - Saravia Otten, Patricia (2004)
ProMMP-2 activation by Bothrops asper venom was investigated in mouse gastrocnemius muscle, mammalian cell culture and a cell-free system. Zymography revealed an increment of latent and activated forms of MMP-2 in muscle homogenates 1–3 days after venom injection. To clarify if venom can induce expression and activation of MMP-2, independently of the inflammatory response, venom was added to cultured human fibroblasts, endothelial and skeletal muscle cells, which expressed proMMP-2 constitutively. Venom activated proMMP-2 without promoting its expression. Venom also activated and degraded proMMP-2 in supernatants collected from fibroblast cultures, indicating that cells are not required for this activation. Pretreatment with EDTA increased MMP-2 activation and reduced degradation. Venom serine proteinases activated proMMP-2, whereas BaP1, a P-I metalloproteinase, predominantly degraded the latent and active forms of MMP-2. Moreover, pretreatment of conditioned medium with serine proteinase inhibitors greatly reduced the venom-induced activation, suggesting that venom proteinases activate MMP-2 via a serine proteinase secreted by fibroblasts. Venom also directly activated and degraded purified proMMP-2, albeit requiring a high concentration. Thus, B. asper venom proteinases activate and degrade proMMP-2 without inducing its synthesis. Serine proteinases play a dominant role in the activation, whereas metalloproteinases predominantly degrade MMP-2. Activation of proMMP-2 by snake venom proteinases, independently of the MT1-MMP/TIMP-2 pathway, extracellular matrix degradation or apoptosis, represents a novel mechanism in human fibroblasts.